Effect of Self-Efficacy and Locus of Control on Employee Performance with Transformational Leadership Style as Moderating Variable - Lukiyana Lukiyana; Meylita Hukom (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of self-efficacy and locus of control on employee performance with transformational leadership as a moderating variable. The population in this study are all employees of companies engaged in interior design who work in Jakarta. The sampling technique used in this research is census, that is, the entire population is used as a sample. The number of samples studied amounted to 255 respondents. Data collection techniques by distributing questionnaires via google form. This research method is quantitative, and data processing uses SmartPLS 3.0 software. The results of this study are self-efficacy has a positive and significant effect on employee performance, locus of control has a positive and significant effect on employee performance, transformational leadership style has a positive and significant effect on employee performance, transformational leadership style is not able to strengthen the influence of self efficacy on employee performance and transformational leadership style are not able to strengthen the influence of locus of control on employee performance. The conclusion from the results of this study is that employee performance is inseparable from self-efficacy, locus of control and transformational leadership style. The high trust of employees, leaders who pay attention to their employees and provide enthusiasm, employee performance will increase.Angelini, C. (2019). Hypothesis Testing. 1, 691–697. https://doi.org/10.1016/B978-0-12-809633-8.20356-7Arif, S. (2019). Influence of Leadership, Organizational Culture, Work Motivation, and Job Satisfaction of Performance Principles of Senior High School in Medan City. Budapest International Research and Critics Institute-Journal (BIRCI-Journal). P. 239-254Ary, I. R., & Sriathi, A. A. A. (2019). Pengaruh Self Efficacy dan Locus Of Control Terhadap Kinerja Karyawan (Studi Pada Ramayana Mal Bali). E-Jurnal Manajemen, 8(1), 30–53. https://doi.org/10.24843/EJMUNUD.2019.v08.i01.p02Bandura, A. (1977). Self-efficacy: toward a unifying theory of behavioral change. Psychological Review, 84(2), 191.Bass, B. M. (1999). Two Decades of Research and Development in Transformational Leadership. European Journal of Work and Organizational Psychology, 8(1), 9–32. https://doi.org/10.1080/135943299398410Bass, B. M., & Riggio, R. E. (2010). The transformational model of leadership. Leading Organizations: Perspectives for a New Era, 2, 76–86.Boye Kuranchie-Mensah, E., & Amponsah-Tawiah, K. (2016). Employee motivation and work performance: A comparative study of mining companies in Ghana. Journal of Industrial Engineering and Management, 9, 255. https://doi.org/10.3926/jiem.1530Chasanah, L. N. (2018). Pengaruh Self Esteem, Self Efficacy dan Locus of Control Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening. Skripsi, 9, 1689–1699.Chen, G., Gully, S. M., & Eden, D. (2004). General self‐efficacy and self‐esteem: Toward theoretical and empirical distinction between correlated self‐evaluations. Journal of Organizational Behavior: The International Journal of Industrial, Occupational and Organizational Psychology and Behavior, 25(3), 375–395.Efendi, R. (2013). Self efficacy: Studi indigenous pada guru bersuku Jawa. Journal of Social and Industrial Psychology, 2(2).Ghozali, I., & Latan, H. (2012). Partial least square: Konsep, teknik dan aplikasi SmartPLS 2.0 M3. Semarang: Badan Penerbit Universitas Diponegoro.Indriasari,  at all. (2019). Pengaruh Locus Of Control Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Etos Kerja Pada Badan Pendapatan Daerah Provinsi Sulawesi Selatan. Journal of Management, 2(3), 1–19. https://doi.org/10.13189/ujm.2016.040404Istiariani, I. (2018). Pengaruh Independensi, Profesionalisme, dan kompetensi Terhadap Kinerja Auditor BPKP (Studi Kasus Pada Auditor BPKP Jateng). Jurnal Islamadina, Vol. 19 No. 1, 19(1), 63–88. https://doi.org/10.30595/islamadina.v19i1.2473Keenan, A., & McBain, G. D. M. (1979). Effects of Type A behaviour, intolerance of ambiguity, and locus of control on the relationship between role stress and work‐related outcomes. Journal of Occupational Psychology, 52(4), 277–285.Khalid, U., Mushtaq, R., Khan, A. Z., & Mahmood, F. (2021). Probing the impact of transformational leadership on job embeddedness: the moderating role of job characteristics. Management Research Review, 44(8), 1139–1156. https://doi.org/10.1108/MRR-05-2020-0260Lukiyana, & Halima. (2016). Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pt. Pacific Metro International Jakarta. Media Studi Ekonomi, 19(2), 56–66. http://journal.uta45jakarta.ac.id/index.php/MSE/article/viewFile/561/343Mangkunegara, A. A. A. P., & Huddin, M. (2016). The Effect of Transformational Leadership and Job Satisfaction on Employee Performance. Universal Journal of Management, 4(4), 189–195. https://doi.org/10.13189/ujm.2016.040404Mangkunegara, A. P., & Octorend, T. R. (2015). Effect of Work Discipline, Work Motivation and Job Satisfaction on Employee Organizational Commitment in the Company (Case Study in PT. Dada Indonesia). Universal Journal of Management, 3(8), 318–328. https://doi.org/10.13189/ujm.2015.030803Mulyani, S. R., Sari, M. W., Sari, V. N., & Tawakalni, W. (2019). The Effect Locus of Control and Organizational Culture Toward Employee Performance with Organizational Commitments as Intervening Variable. JEMA: Jurnal Ilmiah Bidang Akuntansi Dan Manajemen, 16(2), 147. https://doi.org/10.31106/jema.v16i2.2631Narendra, N. M. (2018). Pengaruh Locus of Control dan Komitmen Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja di RSU Al-Islam H. M. Mawardi Sidoarjo. Jurnal Ekonomi Dan Manajemen, 19 No. 2(2), 621–636.Nguyen, T. T., Mia, L., Winata, L., & Chong, V. K. (2017). Effect of transformational-leadership style and management control system on managerial performance. Journal of Business Research, 70, 202–213. https://doi.org/https://doi.org/10.1016/j.jbusres.2016.08.018Niati, D. R., Siregar, Z. M. E., & Prayoga, Y. (2021). The Effect of Training on Work Performance and Career Development: The Role of Motivation as Intervening Variable. Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 4(2), 2385–2393. https://doi.org/10.33258/birci.v4i2.1940Ratnasari, S. L., Sutjahjor, G., & Adam. (2019). Employees’ performance: Organizational culture and leadership style through job satisfaction. Humanities and Social Sciences Reviews, 7(5), 597–608. https://doi.org/10.18510/hssr.2019.7569Rotter, J. B. (1966). Generalized expectancies for internal versus external control of reinforcement. In Psychological Monographs: General and Applied (Vol. 80, Issue 1, pp. 1–28). American Psychological Association. https://doi.org/10.1037/h0092976Safrizal, H. B. A., Eliyana, A., Usman, I., & Gunarsa, F. A. (2020). The effect of transformational leadership on job satisfaction: The mediation effect of self-efficacy and work engagement. Systematic Reviews in Pharmacy, 11(8), 166–177. https://doi.org/10.31838/srp.2020.8.26Santhidran, S., Chandran, V. G. R., & Borromeo, J. (2013). Enabling organizational change-leadership, commitment to change and the mediating role of change readiness. Journal of Business Economics and Management, 14(2), 348–363. https://doi.org/10.3846/16111699.2011.642083Saputri, M. E. (2016). Pengaruh Perilaku Konsumen Terhadap Pembelian Online Produk Fashion Pada Zalora Indonesia the Effect of Consumer Behavior Toward the Online Purchase of Fashion Product of Zalora Indonesia. Sosioteknologi, 15(2), 291–297.Septyan, F. B. (2017). Pengaruh Gaya Kepemimpinan Transformasional Terhadap Motivasi Dan Kinerja (Studi Pada CV. Jade Indopratama Malang). Universitas Brawijaya.Simbolon, N. L., & Priyonggo, B. S. (2022). Analysis of the Effects of Self-Efficacy Mediation and Organizational Commitment on the Effect of Transformational Leadership Style and Organizational Culture on Employee Performance of PT Sarana Lintas Caraka. Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 5, 6611–6624. https://doi.org/10.33258/birci.v5i1.4387Soleh, A., Noviantoro, R., & Putrafinaldo, D. (2020). The effect of locus of control and communication toward employee performance. MSDJ : Management Sustainable Development Journal, 2, 41–51. https://doi.org/10.46229/msdj.v2i2.184Sugiyono, D. (2018). Metode penelitian kuatintatif, kualitatif dan R & D/Sugiyono. Bandung: Alfabeta, 15(2010).Sugiyono, P. D. (2009). Metode Penelitian Kuantitatif Kualitatif Dan R&D, Bandung: Cv. Alvabeta.Sugiyono, P. D. (2017). Metode penelitian bisnis: pendekatan kuantitatif, kualitatif, kombinasi, dan R&D. Penerbit CV. Alfabeta: Bandung, 225.Wahjudewantia, A. S., Tjakraatmajaa, J. H., & Anggoroa, Y. (2021). Knowledge Management Strategies to Improve Learning and Growth in Creative Industries: A Framework Model. Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 4(2), 1903–1915. https://doi.org/10.33258/birci.v4i2.1876Wijanto, S. H. (2008). Structural equation modeling dengan Lisrel 8.8. Yogyakarta: Graha Ilmu.Wulandari, R., Djawoto, D., & Prijati, P. (2021). The Influence of Delegative Leadership Style, Motivation, Work Environment on Employee Performance in Self-Efficiency Mediation in SNVT Housing Provision of East Java Province. Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 4(3), 3294–3311.Yusup, F. (2018). Uji Validitas dan Reliabilitas. Jurnal Tarbiyah: Jurnal Ilmiah Kependidikan, 7(1), 17–23. https://jurnal.uin-antasari.ac.id/index.php/jtjik/article/download/2100/1544Zulkosky, K. (2009). Self-Efficacy: A Concept Analysis. Nursing Forum, 44(2), 93–102. https://doi.org/10.1111/j.1744-6198.2009.00132.x